Freewater - Luqman-Dawson, Amina (Little, Brown and Company, 2022)
After they flee the plantation where they were enslaved, twelve-year-old Homer and his sister Ada find a home with the people of Freewater, a group of escaped slaves who secretly live in the Great Dismal Swamp. There he finds a new community of friends who support one another to ensure they remain free. When their community is threatened, Homer hatches a plan to rescue his enslaved mother and ensure the safety of Freewater residents.